Evaluation of Antimicrobial Efficiency of Bipyrimidines Using Zeolite as a Green Catalyst in Biphasic System - Manisha S. Aswale; Raksha P. Dhankar (Recent Developments in Chemistry and Biochemistry Research Vol. 3, 2024)
In the present study, we have designed and synthesized a new series of bipyrimidines by simple condensation and screened them for their in vitro antimicrobial activities. Current research has depicted the efforts towards the utilization of biphasic reaction systems in the synthesis of a variety of heterocycles. This shows the remarkable importance of the monophasic solvent system. A simple, green and efficient catalytic condensation process has been developed to synthesize the series of 2-amino-6-substituted- 4,6-diphenyl-3’,4,4’,5-tetrahydro[4,5’-bipyrimidine]-2’(1H)-one (3a- j) hybrids. The catalytic route was investigated efficiently in the presence of NaY zeolite in an organic-aqueous (dichloromethane-water) solvent system. In this method, biphasic solvent systems were explored for suitable applicability where catalyst exhibits remarkable reactivity. The synthesized scaffolds of bipyrimidines were studied as anti-microbial agents. The investigation of antimicrobial screening data revealed that among 10 compounds screened, compounds 3d, 3e, 3f and 3i demonstrated very good activity as compared to standard drugs and the remaining compounds showed good to moderate inhibition activities. Synthesized compounds were screened for their in vitro antibacterial activity against Staphylococcus aureus, E. coli and Pseudomonas aurigenosa and also antifungal activity against the opportunistic pathogens Candida albicans and Aspergillus niger.